Consumer Protection in Contemporary Business Structures: About Contractual Connectedness in Consumer Contracts - Frustagli, Sandra A. (2023)
This paper analyzes the legal consequences of the contractual connection in consumer contracts from the perspective of the Argentine legal system. It takes into consideration that the Civil and Commercial Code provides its own normative regime for the consumer contract as a business category different from the parity contract. However, since the rules governing the contractual connection are methodologically located within the general theory of contract, the application of that regime to related consumer contracts must be made in the light of the pro-consumer principle, of constitutional hierarchy (article 42 of the National Constitution CN), in order to guarantee the fundamental right to the protection of its economic interests. This leads to the recognition of a regime of actions in favor of the consumer that is broader than that which emerges from articles 1073 to 1075 of the Civil Code for related contracts in general.